2003
DOI: 10.1097/00001756-200308060-00020
|View full text |Cite
|
Sign up to set email alerts
|

Self-administration of 5-iodo-A-85380, a β2-selective nicotinic receptor ligand, by operantly trained rats

Abstract: It is widely accepted that nicotine is the active ingredient of tobacco smoke that promotes tobacco dependence. Nicotine interacts with several subtypes of nicotinic acetylcholine receptors (nAChRs). In brain, it primarily targets nAChRs that contain beta2 and alpha4 subunits in combination and those composed of solely alpha7 subunits. The present study tested whether operantly trained rats would self-administer a ligand active at beta2-containing (i.e. not alpha7) nAChRs. Male Sprague-Dawley rats were trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
5
23
0
Order By: Relevance
“…Whereas nicotine reinforcement and reward-like behavior require activation of β2*nAChRs [21][27], [29][32], [52], the studies described herein suggest that inactivation of β2*nAChRs decreases fear-like and anxiety-like behavior as measured by increased suppression ratios during CER, decreased digging behavior in a marble burying task, and increased exploratory behavior in the open arms of an elevated plus maze. Rats will self-administer A-85830, a selective agonist of β2*nAChRs [52]. Administration of selective β2*nAChR antagonists blocks nicotine conditioned place preference and greatly attenuates nicotine self-administration [21][25].…”
Section: Discussionmentioning
confidence: 60%
“…Whereas nicotine reinforcement and reward-like behavior require activation of β2*nAChRs [21][27], [29][32], [52], the studies described herein suggest that inactivation of β2*nAChRs decreases fear-like and anxiety-like behavior as measured by increased suppression ratios during CER, decreased digging behavior in a marble burying task, and increased exploratory behavior in the open arms of an elevated plus maze. Rats will self-administer A-85830, a selective agonist of β2*nAChRs [52]. Administration of selective β2*nAChR antagonists blocks nicotine conditioned place preference and greatly attenuates nicotine self-administration [21][25].…”
Section: Discussionmentioning
confidence: 60%
“…In the same report, nicotine was effective in provoking reward behavior in 7 knockout mice, but not in 2 knockout mice [172]. Furthermore, rats will self administer the selective 4 2 agonist A-85380, suggesting that this compound also has rewarding effects [173]. Infusion of DH E into the ventral tegmental area, a part of the mesolimbic dopamine system that is associated with reward, blocks nicotine mediated self administration and dopamine release [174,175].…”
Section: Dependencementioning
confidence: 92%
“…Recent results have shown that 5IA is also a potent activator of a6b2* receptors in vitro (Mogg et al, 2002), and based on this finding it is now generally referred to as b2*-selective nicotinic receptor ligand (Liu et al, 2003). Thanks to its high-affinity, low nonspecific binding, and lack of toxicity in mammals, 5IA has been characterized as a tool for noninvasive in vivo studies of b2* nicotinic receptor (Vaupel et al, 1998(Vaupel et al, , 2005.…”
Section: Figurementioning
confidence: 99%